Comparison of effect of machine muteness to reduce noise anxiety vs regular settings on patient compliance during pan-retinal photocoagulation - Anam, Amna; Malik, Irfan Qayyum; Hameed, Zeeshan (Journal of the Pakistan Medical Association, 2024)
This Quasi Experimental study was conducted at Major Eye Clinic, Gujranwala, from January to December 2022, to study the effect of muting the sound of Argon Laser machine on patient compliance and the pain felt during pan-retinal photocoagulation (PRP). Eighty patients were included in the study with proliferative diabetic retinopathy (PDR), retinal breaks, lattice and myopic fundus degenerations for which PRP was performed. A total of 80 patients were enrolled, who were divided in two groups with 40 patients in each group. Group A patients received muted machine settings, while group B underwent regular PRP. The mean age was 54.6±3.4 years. Sixty-eight (85%) cases were of PDR, 4 (5%) of retinal breaks, 3 (3.75%) of lattice degenerations associated with breaks, and 5 (6.25%) of laser barrage. —Continue